Characterization of Potato Virus M epitopes with the use of synthetic peptides - Viter, S.S.; Tkachenko, T.Yu.; Kolomietz, L.P.; Radavsky, Yu.L. (Біополімери і клітина, 2001)
As a result of thermolysin hydrolysis of a coat protein (CP) of Potato Virus M Ukrainian Strain VI (PVM), the heptapeptide ²⁹AADFEGK³⁵ was found to be recognised by two PVM specific monoclonal antibodies (MAbs) M6D5 and M9G1. This heptapeptide represents the C-terminal part of tryptic tetradecapeptide ²²EARPLPTAADFEGK³⁵ (P14) which was also recognised by the same MAbs. The peptides represented sequences of tryptic (P14), thermolysinic (P7) fragments and three heptapeptides containing alanine substitutions for Asp³¹ and Glu³³, were synthesised to determine the contribution of dicarbonic amino acids in the antigen-antibody interaction. All synthetic heptapeptides were recognised by both MAbs weakly in indirect ELISA. These peptides were also used as inhibitors of MAb-CP and MAb-P14 reactions in inhibition ELISA. The results of inhibition ELISA have shown the following: 1) the same concentrations of peptides were more effective to inhibit the interaction of MAbs with P14 than with CP; 2) substitutions of charged amino acids decreased noticeably the ability of peptides to inhibit the antigen-antibody interaction, especially the substitution of Asp³¹ ; 3) heptapeptides containing alanine substitutions suppressed more effectively the interaction of MAb M6D5 with antigens and were less effective to inhibit the reaction of MAb M9G1 with the same antigens. Thus, the difference in Asp³¹ and Glu³³ contributions to the antigen-antibody complex formation has been found. После гидролиза белка оболочки (БО) украинского штамма Ul М-вируса картофеля (PVM) термолизином выделен фрагмент 29AADFEGK³⁵ , распознаваемый двумя моноклональными антителами (MKA) M6D5 и M9G1, специфичными к PVM. Этот гептапептид представляет собой С-концевой участок триптического тетрадекапептида ²²EARPLPTAADFEG³⁵ (П 14), распознаваемый этими же MKA. Для определения вклада отрицательно заряженных дикарбоновых аминокислот в формирование комплекса антиген–антитело синтезированы синтетические пептиды, повторяющие последовательности триптического (П14) и термолизинового (П7) фрагментов, а также гептапептиды, содержащие замены Asp³¹ и Glu³³ на аланин. Все синтетические гептапептиды слабо взаимодействовали с обоими MKA в непрямом ИФА. Эти пептиды были использованы в качестве ингибиторов реакций МКА-БО и МКА-П 14. Результаты ингибирования ИФА показали, что: 1) одинаковые концентрации пептидов эффективнее ингибировали взаимодействие MKA с П14, чем с Бр; 2) замена заряженных аминокислот, особенно замена Asp³¹ и Glu³³ вносят различный вклад в формирование комплекса антиген–антитело. Після гідролізу білка оболонки (БО) українського штаму Vl M-вірусу картоплі (PVM) термолізином виділено фрагмент 29AADFEGK³⁵ , який розпізнавався двома моноклональними антитілами (MKA) M6D5 та M9G1, специфічними до PVM. Цей гептапептцд є С-кіщевою частиною триптичного тетрадекапептиду ²²EARPLPTAADFEGK³⁵ (П14), який розпізнавався тими самими MKA. Для визначення внеску негативно заряджених дикарбонових амінокислот у формування комплексу антиген–антитіло синтезовано синтетичні пептиди, що повторюють послідовності триптичного (П14) та термолізинового (П7) фрагментів, а дгакож гептапептиди, які містили заміни Asp³¹ та Glu³³ на аланін. Усі синтетичні гептапептиди слабко взаємодіяли з обома MKA в непрямому ІФА. Ці пептиди використовували як інгібітори взаємодії MKA-БО і МКА-П14. Результати інгібування ІФА показали, що: 1) однакові концентрації пептидів ефективніше інгибують взаємодію MKA з П14, ніж із БО; 2) заміна заряджених амінокислот, особливо заміна Asp³¹ , значно зменшує здатність пептидів пригнічувати взаємодію антиген–антитіло; 3) гептапептиди, що містять заміни амінокислот на аланін, ефективніше пригнічують взаємодію MKA M6D5 з антигенами та набагато слабше інгібують реакщір MKA M9G1 з тими самими антигенами. Таким чином, Asp³¹ та Glu³³ по-різному впливають на формування комплексу антиген–антитіло.